Functional characterization of Huntington's disease cases in a brazilian municipality (Research, Society and Development, 2021)
Huntington's disease (HD) is a neurodegenerative disorder of autosomal dominant inheritance. The symptoms are characterized by a triad, movement disorder, mood changes, and cognitive impairment. This is a cross-sectional, descriptive study, aiming to identify the functional status of HD patients, from a census sample, analyzing all patients diagnosed in the municipality. The research was carried out in a city of Alagoas, with twenty individuals diagnosed with the disease. To achieve the objectives, we used a questionnaire validated for the Brazilian population, the Functional Independence Measure (FIM), which identifies the dependence of a person on their functional capacity, assessing the difficulty in performing self-care tasks, mobility and communication. From the analysis of the results it was possible to identify the existing family relationships, the type of medical and rehabilitation assistance that each participant is submitted to, and their functional condition, leading the researchers to characterize each of them and conclude that the limitation in access to specialized services in physical rehabilitation and the absence of genetic counseling leads to the continuity of cases and the high prevalence of this pathology in the city.